La homocisteína y la enfermedad cardiovascular (2006)
ABSTRACT: Homocysteine is a no essential sulfured aminoacid, that contains a thiol group in its structure. The homocysteine is produced in almost all human tissues for the methionine metabolism. In 1990, The Framingham study, demostrated that homocysteine (Hcy) could be a possible risk factor for cardiovascular disease. Since 2003 Hcy has been considered an “emergent” risk factor. The hiperhomocysteinemia is defined when plasmatic levels of total Hcy is above of 15 μmol/L. It`s classified according to three severity stages, moderate 15-30 μmol/L, intermediate 31-100 μmol/L and severe, higher than 100 μmol/L. Hiperhomocysteinemia can be produced by enzymatic deficiency in any of its metabolic routes, and also due to low plasmatic levels of folic acid, vitamins B6 or B12 and renal failure, because kidney is the main organ to eliminate the Hcy from plasma. Folic acid diet supplementation could reduce Hcy blood concentration about 25%, and supplementation with vitamin B12 about 7%, however the supplementation with vitamin B6 has not shown any effect. Healthy life style, quit smoking, and balanced diet with a moderate consumption of coffee and alcohol may reduce Hcy plasmatic levels.